Determination of Time and Cost Deviations on the Example of the Residential Construction Project in Štinjan (Proceedings of Faculty of Civil Engineering, 2022)
The aim of work is to present a model for monitoring the construction time and cost aspects of terraced houses in Štinjan. The model will include the development of a structural breakdown of the project, planned cost curve and time plan of works using the method of past activities. In addition to the curve of planned values, the curve of realized values will also be created. The identified deviations will be analyzed, the risks that caused them will be identified, and appropriate measures, to reduce or eliminate the deviations, shall be proposed.
Keywords: construction project; risks; overrun; cost curve; time plan